Laddering : unlocking the potential of consumer behavior - Holtzclaw, Eric V., 1973- (John Wiley & Sons, Inc., 2013)
Marketing and product development best practices for a fragmented economy The rules for marketing and product development have changed forever. You no longer control where and how consumers receive marketing messages. The consumer is in charge, with ever-growing choices and a shrinking decision window. Therefore, it is crucial to understand what drives customer behavior to design products, marketing, and experiences that will succeed. Laddering explains how to better understand your customers' core values. Learn to ask the right questions from your customers, use it to analyze.